KOMUNIKASI TEKNOLOGI MASYARAKAT TEPAS TANDHA YEKTI KERATON YOGYAKARTA [TECHNOLOGY AND COMMUNITY COMMUNICATION FOSTERED BY TEPAS TANDHA YEKTI IN THE YOGYAKARTA ROYAL PALACE] - Andreina Caniggia (Polyglot, 2020)
The flow of technology is rapidly penetrating the walls of the Yogyakarta Royal Palace tradition as it becomes a bridge of communication, disseminating information about culture, education, and ancestral messages. In response to the changing times, the Yogyakarta Royal Palace is evolving in terms of community technology communication with the establishment of a new division of IT and documentation, Tepas Tendha Yekti, under the auspices of the sultan's daughter, GKR Hayu. This research focuses on new media in terms of technology and community communication fostered by Tepas Tendha Yekti.BAHASA INDONESIA ABSTRACT: Arus teknologi semakin pesat menembus tembok tradisi Keraton Yogyakarta untuk menjadi jembatan komunikasi, menyebarluaskan informasi mengenai budaya, pendidikan, serta pesan leluhur. Pengalihan zaman menuntut Keraton Yogyakarta untuk berevolusi dalam segi komunikasi teknologi masyarakat dengan hadirnya divisi baru, divisi IT dan dokumentasi Tepas Tendha Yekti, di bawah naungan seorang anak perempuan sultan, GKR Hayu. Penelitian ini memfokuskan media baru dalam segi komunikasi teknologi dan masyarakat yang dibina oleh Tepas Tendha Yekti.